(untitled) (Physical Education, Health and Social Sciences, 2025)
Social media has accelerated the prevalence of unfriending and selective exposure making it a matter of major concern when it comes to political polarization in modern democracies. This paper focuses on the association between political polarization and unfriending behavior on social media and the moderating effect of education in this association is considered. Based on the results of the surveys with adult social media users, the concept of political polarization is represented as a cohesive category that includes issue-based and ideological polarization. Based on the reliability analysis, correlation analysis, and the hierarchical regression modeling, the results show that political polarization is a significant and positive predictor of the unfriending behavior meaning that people with more polarized political views have higher chances of removing or avoiding politically dissimilar other people online. Moreover, moderation analysis shows that the influence of education on this relationship is important, whereby, the impact of political polarization of unfriending is less significant in those who possess higher education. These findings indicate that education can be a mediating force as it can promote tolerance towards political disagreement and exposure to different opinions. The research also adds to the developing body of literature about the topic of digital political behavior by incorporating various aspects of polarization into one explanatory model and by emphasizing the protective quality of education to restrain socially disintegrating online activities. Policymakers, educators, and platform designers are discussed in the context of practical implications pertaining to curbing polarization-induced social fragmentation in online platforms.